Applications of two-dimensional materials in food packaging. (April 2021) - Yu, Yadong; Zheng, Jie; Li, Jingchen; Lu, Lingxia; Yan, Jinyuan; Zhang, Lihui; Wang, Longfeng
Abstract: Background: The expectations for high food safety and quality keep rising in modern societies, driving food packaging technologies to evolve continuously. Recently, two-dimensional materials (2DMs) with some fascinating properties such as large specific surface area, high mechanical performance and unique electrocatalytic activity, have been widely explored for various applications including food packaging. Scope and approach: This review summarizes recent advances regarding the applications of 2DMs (including graphene, transition metal dichalcogenides (TMDs), hexagonal boron nitride (h-BN), layered double hydroxides (LDHs), graphitic carbon nitride (g-C3 N4 ), transition metal carbides and nitrides (MXenes)) in active packaging (such as improving the barrier property, mechanical property, thermal stability and antimicrobial activity, etc.) and intelligent packaging (such as preparing leak indicators, pH indicators, time-temperature indicators, gas sensors, intelligent labels, etc.). Current research gaps and future prospects of this field are discussed as well. Key findings and conclusions: Increasing numbers of studies have proven the versatility of 2DMs in food packaging. Yet, the potentials of 2DMs are still not fully explored, even the most reported graphene and its derivatives. In order to make 2DMs-based food packaging technologies commercially viable, some aspects such as cost, legislation, consumers' acceptance, as well as the migration behaviors and toxicology of 2DMs in packaging materials need more considerations and explorations. Graphical abstract: Image 1 Highlights: Applications of 2D materials in active packaging are summarized. Applications of 2D materials in intelligent packaging are summarized. Current research gaps and future prospects of this field are discussed.